Functional characterization of NAD dependent de-acetylases SIRT1 and SIRT2 in B-Cell Chronic Lymphocytic Leukemia (CLL). Issue 3 (3rd March 2016) - Bhalla, Savita; Gordon, Leo I.
ABSTRACT: Sirtuins (SIRT) are nicotinamide adenine dinucleotide (NAD+) dependent deacetylases or ADP- ribosyl transferases (ARTs) that deacetylate lysine residues on various proteins regulating a variety of cellular and metabolic processes. These enzymes regulate metabolism, cell survival, differentiation and DNA repair. SIRT proteins play an important role in the survival and drug resistance of cancer cells. The purpose of the present study was to investigate the expression and role of SIRT in chronic lymphocytic leukemia (CLL). We analyzed the expression of SIRT1 and SIRT2 in CLL and normal B cells using the Oncomine database as well as by Western blotting of fresh CLL cells from patients and pro-lymphocytic leukemia (PLL) cell lines, JVM-3 and MEC-2. We showed that both primary CLL cells and JVM-3 and MEC-2 cell lines overexpress high levels of functional SIRT1 and SIRT2. SIRT inhibitors EX-527 and sirtinol impair cell growth, induce ROS production, loss of mitochondrial membrane potential and apoptosis in primary CLL cells and cell lines. Using shRNA knock down of SIRT1 and SIRT2 in JVM-3 and MEC-2 cell lines, we showed that expression of both proteins is crucial for the survival of these cells. Furthermore, studies in nutrient deprived conditions suggest a role of SIRT in metabolism in CLL. These results demonstrate that the inhibition of SIRT1 and SIRT2 activity may be a new therapeutic approach for CLL.